FAKTOR FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN DALAM PEMBELIAN DI DISTRO POLOSANYK - Irvan Yulian Hernandi; Muhammad Awal Satrio Nugroho (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2023)
Consumers who are satisfied with products and services tend to repurchase products and reuse services when the same needs reappear in the future. This means that satisfaction is a key factor for consumers in making repeat purchases which constitute the largest portion of the company sales volume. To determine the factors that influence consumer satisfaction in purchasing at Polosanyk distributions. The type of research used is descriptive quantitative research. The population in this study were all consumers of Polosanyk distribution in January and February 2022 with a sample of 81 people. The data analysis of this research used multiple regression analysis. There is a significant effect of product quality on consumer satisfaction in Polosanyk distributions. This is evidenced by the t-count value of 2.778 and a significance value of 0.007 which is smaller than 0.05. There is no significant effect of service quality on consumer satisfaction in Polosanyk distributions. This is evidenced by the t-count value of -0.177 and a significance value of 0.860 which is greater than 0.05. There is no significant effect of store atmosphere on consumer satisfaction in Polosanyk distributions. This is evidenced by the t-count value of 1.947 and a significance value of 0.299 greater than 0.05. There is a significant effect of price on consumer satisfaction in Polosanyk distributions. This is evidenced by the t-count value of 4.611 and a significance value of 0.000 which is less than 0.05. There is a significant effect of product quality, service, store atmosphere and price on consumer satisfaction in Polosanyk distributions. This is evidenced by the t-count value of 11.992 and a significance value of 0.000 which is less than 0.05.